SOME DYNAMIC ASPECTS OF THE NUCLEAR ENVELOPE - Merriam, R. W. (The Rockefeller University Press, 1962)
Nuclei of frog oocytes were isolated, fixed in OsO(4) or KMnO(4), and washed. Nuclear envelopes were then dissected off, placed on grids, and air-dried for electron microscopy. Envelopes from immature oocytes at the stage of beginning yolk deposition were compared with those from mature oocytes. Envelopes from the immature stage had "pores" whose annuli contained more material and showed central globules in the center much more frequently than envelopes from mature eggs. Annuli and central globules had similar appearance and fixation properties, suggesting similar chemical composition. After fixation with KMnO(4), residual densities suggested that "pore" diaphragms are much more variable in thickness or composition in the younger stages. Envelopes of the immature oocytes had about 40 per cent more "pores" per unit area than mature envelopes. In crowding together, the "pores" tended to assume geometrical packing arrays in the young envelope, showing minimum center-to-center spacings of about 1530 A. Since the actual discontinuities in the membranes of the envelope are only about 950 A in diameter, this minimum distance of approach suggests that adjacent formations of the nuclear surface are associated with "pore" structure and perhaps set their limiting spacing distances. If this is true, then it can be deduced that "pore"-associated structures of the nuclear surface are probably circular in outline and about 1500 A in diameter. Isotopically labeled lysine was administered to intact, growing oocytes for 1 to 4 hours and the envelopes were subsequently isolated and fixed. Autoradiography of entire envelopes showed little or no incorporation of lysine into proteins, as compared with small fragments from other parts of the cell of roughly comparable mass. It was concluded that the isolated envelope, as seen in the electron micrographs, does not synthesize or turn over lysine-containing protein at a high rate.